Leech parasitism of waterfowl in the British Isles - Elliott, J M; Tullett, P A (Wildfowl, 1982)
Two species of leeches, Haementeria (= Placobdella) costata and Theromyzon tessulatum, attack waterfowl in the British Isles. H. costata has been found at only one locality in Britain. T. tessulatum is common and has been recorded on 20 species of water-birds. Information on the effects of the leeches on their hosts is reviewed, and occurrence records for the British Isles are summarized. The life cycle of T. tessulatum is described, and some comparisons are made with other studies on this species.